مدى تبنى القضاء الإدارى الأردنى لنظرية العلم اليقينى: دراسة مقارنة - الكساسبة، هشام حامد; الرواشدة، القاضى وسن فيصل; الشباطات، محمد علي زعل (مركز البحث وتطوير الموارد البشرية - رماح, 2020)
أن نشر القرار الإداري أو إعلانه إلى صاحب الشأن يعتبر قرينة قانونية غير قابلة لإثبات العكس على العلم بالقرار سواء كان تنظيميا أو فرديا، إلا أن ذلك لا يمنع من إثبات وصول العلم للمخاطب بالقرار بدون هذه الوسائل، وذلك اعتمادا على أي وسيلة من وسائل الإخبار الكافية على ثبوت العلم اليقيني، فالعلم الحقيقي يتحقق إذا لم تلجأ الإدارة إلى الأساليب السابقة متى حالت الظروف دون ذلك، أو كان من شأنها أن تحول دون إتباعها، وبناء عليه يتناول البحث مدى تبني القضاء الإداري الأردني لنظرية العلم اليقيني، فقد نص المشرع على هذه الحالة والحقها بالنشر والإعلان لاتحاد العلة، وذلك حتى لا يظل أمر القرارات التي لم تنشر أو لم تُعلن معلقا إلى أمد غير محدد، وبما يستتبع ذلك عدم الاستقرار في المراكز القانونية المترتبة على هذه القرارات، لذلك أضاف القضاء الإداري إلى وسيلتي النشر والإعلان المنصوص عليهما قانونا وسيلة ثالثة هي العلم اليقيني، ولهذا جاء البحث على النحو الآتي: المبحث الاول ماهية العلم اليقيني وفي المطلب الأول منه مضمون العلم اليقيني والثاني الشروط اللازم توافرها بالعلم اليقيني والثالث موقف الفقه من العلم اليقيني، وفي المبحث الثاني إثبات العلم اليقيني وفي المطلب الأول منه وسائل إثبات العلم اليقيني والمطلب الثاني مدى قوة قرينة العلم اليقيني في الأثبات.
The promulgation or announcement of the administrative decision to the concerned party is deemed a legal, irreversible presumption on serving the decision whether it was regulatory or individual. Yet, this does not prevent proving that the concerned party had been communicated the decision without these means, depending on any of the sufficiently accepted notification or serving methods that provide a proof on the indisputable knowledge. The actual knowledge will be achieved if the administration did not apply the abovementioned methods, once certain circumstances prevent them, or such circumstances would prevent applying these methods. Accordingly, the research deals in the extent of the Jordanian administrative judicature adoption of the indisputable knowledge. In this concern, the legislator provided this case and attached it to the publishing and announcement due to the integration of causality. This is vitally important so that the case of the unannounced or unpublished decision will not remain pending for indefinite periods, which, consequently, will result in instability of the legal positions concerned with these decisions. As such, the administrative judiciary added to the two legally specified publishing and announcement methods a third method, i.e. the indisputable knowledge. Thus, this research was made as follows: the first topic, "Essence of the Indisputable Knowledge", which included three requirements: content of the indisputable knowledge, the conditions that should be present in the indisputable knowledge, and jurisprudence attitude toward the indisputable knowledge. The second topic, "Proof of the Indisputable Knowledge", tackled two demands: means of proving the indisputable knowledge, and strength of the indisputable knowledge presumption in evidencing.
Keywords: العلم اليقينى -- القضاء الإدارى -- الدعوى الإدارية -- القرائن القضائية